Performance assessment using sensor technology. Issue 2 (10th July 2021) - Mohamadipanah, Hossein; Wise, Brett; Witt, Anna; Goll, Cassidi; Yang, Su; Perumalla, Calvin; Huemer, Kayla; Kearse, LaDonna; Pugh, Carla
Abstract: Over the past 30 years, there have been numerous, noteworthy successes in the development, validation, and implementation of clinical skills assessments. Despite this progress, the medical profession has barely scratched the surface towards developing assessments that capture the true complexity of hands‐on skills in procedural medicine. This paper highlights the development implementation and new discoveries in performance metrics when using sensor technology to assess cognitive and technical aspects of hands‐on skills.